Impact of Capital Structure on Organizational Success on pharmaceutical industries in Nepal (SNPRC Journal, 2023)
Capital structure decision is an important prerequisite to becoming a successful organization. The current study focuses on the relationship between capital structure and organizational success. It also tries to investigate the impact of capital structure on organizational success. Data was collected from three pharmaceutical industries i.e. Asian Pharmaceutical, Siddartha Pharmaceutical, and Grace Pharmaceutical. Debt and equity were used as independent variables and sustainability, market growth, and competitive advantages were used as dependent variables structured questionnaires were used and 100 questionnaires were distributed but the data could be only collected from 86 respondents. SPSS version 25 and Microsoft Excel were used for data management. This research implements a correlational research design with descriptive and explanatory research design. Mean analysis has been used to explain the position of variables. Correlation and regression analysis have been used to explain the relationship between variables. The positions of the capital structure were at optimum level and the position of sustainability, market growth, Competitive Advantages, and overall organizational success is above satisfactory. Capital structure decisions significantly impact the success of the Organization.